2021
DOI: 10.1002/essoar.10508718.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How much inundation occurs in the Amazon River basin?

Abstract: The Amazon River basin harbors some of the world's largest wetland complexes, which are of major importance for biodiversity, the water cycle and climate, and human activities. Accurate estimates of inundation extent and its variations across spatial and temporal scales are therefore fundamental to understand and manage the basin's resources. More than fifty inundation estimates have been generated for this region, yet major differences exist among the datasets, and a comprehensive assessment of them is lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 173 publications
0
5
0
Order By: Relevance
“…Meanwhile, the threshold of 1 is inadequate to conclude the water presence because any dataset can have commission error. If we have 20 datasets instead of three as now, we will have more choices of thresholding, and what would be obtained finally can be even more reliable (Fleischmann et al, 2021).…”
Section: Monthly Water Extentmentioning
confidence: 99%
“…Meanwhile, the threshold of 1 is inadequate to conclude the water presence because any dataset can have commission error. If we have 20 datasets instead of three as now, we will have more choices of thresholding, and what would be obtained finally can be even more reliable (Fleischmann et al, 2021).…”
Section: Monthly Water Extentmentioning
confidence: 99%
“…Several remote sensing-derived Amazon flood extent databases have been developed in recent years to characterize flooding in Amazon (Fassoni-Andrade et al, 2021). This is not a trivial mapping and the different approaches have led to disagreements, as shown by the comparison documented in Fleischmann et al (2022). We used two basin-scale databases that consider periods of maximum and minimum inundation Rosenqvist et al, 2020).…”
Section: Modelling Performance Metricsmentioning
confidence: 99%
“…However, it is noteworthy that the various remote sensing-derived water extent databases also have large inconsistencies among them. For example, Fleischmann et al (2022) showed that HESS and ALOS mapping tend to underestimate the maximum inundation compared to subregional remote sensing-derived products, and there are large differences in minimum inundation among the different products.…”
Section: Flood Extentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the places most dramatically affected by seasonality is Central Amazonia. This incredibly biodiverse and food rich environment for humans experiences a marked seasonal hydrological cycle (Fleischmann et al 2021). Characterized by a smooth and predictable ood curve with one pronounced peak per year, it is one of the largest seasonal uctuations in water level on earth.…”
Section: Introductionmentioning
confidence: 99%